Ig-score, Investment Account Holders, Jumlah Dewan Komisaris Independen, Dan Corporate Social Responsibility Pada Perbankan Syariah Yang Terdapat Di Indonesia - Charatunnisa Charatunnisa; Muthmainah Muthmainah (SEKOLAH TINGGI ILMU EKONOMI NGANJUK, 2019)
This study aims to find out and obtain empirical evidence whether there are factors that influence the level of disclosure of Corporate Social Responsibility in Islamic banking in Indonesia. The researcher performed an independent variable in the form of Islamic Governance Score, Investment Account Holder, and the number of Independent Board of Commissioners did have an influence on the dependent variable Corporate Social Responsibility with control variables with multiple company sizes calculated based on total assets. Disclosure of CSR in sharia banking is measured using a disclosure index found in AAOIFI, IG-Score is calculated based on scoring on several indicators, IAH is calculated based on total temporary syirkah funds divided by total equity and the Number of Independent Commissioners is calculated by comparing the total Independent Commissioners and the entire Board Commissioner. This study uses a sample of 61 observations from companies registered with the OJK in the period 2013-2017. The results of the study provide empirical evidence that the Islamic Governance Score negatively affects the level of disclosure of Corporate Social Responsibility, Investment Account Holder has a positive effect on the level of disclosure of Corporate Social Responsibility and the Number of Independent Commissioners does not affect the level of disclosure of Corporate Social Responsibility in Islamic banking in Indonesia . Based on the results of this study, it implies that with the positive influence of Investment Account Holders on Corporate Social Responsibility companies can better monitor and increase investment efficiently and the resulting implications can also be beneficial for the government so that it can oversee Corporate Social Responsibility activities.